2016
DOI: 10.1186/s13059-016-1099-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the morbid genome of ciliopathies

Abstract: BackgroundCiliopathies are clinically diverse disorders of the primary cilium. Remarkable progress has been made in understanding the molecular basis of these genetically heterogeneous conditions; however, our knowledge of their morbid genome, pleiotropy, and variable expressivity remains incomplete.ResultsWe applied genomic approaches on a large patient cohort of 371 affected individuals from 265 families, with phenotypes that span the entire ciliopathy spectrum. Likely causal mutations in previously describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
156
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 142 publications
(169 citation statements)
references
References 43 publications
12
156
0
1
Order By: Relevance
“…Consistent with our prior experience in the study of genetics of recessive diseases, [21][22][23][24][25][26] we found a high hit rate of exome sequencing in the study cohort. Although recurrence in our cohort was not selected on the basis of autosomal recessive inheritance (some families had maleonly affected members), our analysis did not reveal any X-linked mutations.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our prior experience in the study of genetics of recessive diseases, [21][22][23][24][25][26] we found a high hit rate of exome sequencing in the study cohort. Although recurrence in our cohort was not selected on the basis of autosomal recessive inheritance (some families had maleonly affected members), our analysis did not reveal any X-linked mutations.…”
Section: Discussionsupporting
confidence: 90%
“…Patient 4 with the apparently more severe genotype (nonsense mutation) had more extensive phenotype. This is similar to the report by Shaheen and colleagues where a patient with a severe EXOC3L2 mutation (homozygous frameshift and early truncation, p.Leu134Thrfs*25) had renal and neurological phenotype (DWM and MGS) 26. Nevertheless, patient 4 had milder poster fossa malformations than that of the patients with missense mutations.…”
Section: Discussionsupporting
confidence: 90%
“…A single subject had posterior fossa malformations (not further specified) and a homozygous variant in EXOC3L2 . The kidney disease in both, patient 4 and the first published case,26 strengthens the link of EXOC3L2 also with early-onset severe renal failure.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Homozygous mutations in the TXNDC15 gene causing MKS have been reported in one publication, where MKS was described in three consanguineous families: two Saudi and one Pakistani (Shaheen et al, ). The prenatal findings in one stillbirth were typical for MKS: polydactyly, enlarged cystic kidneys, and occipital encephalocele.…”
Section: Discussionmentioning
confidence: 99%